Erythrokeratodermia variabilis Cram-Mevorah - Bonifazi, E.; Milano, A. (European Journal of Pediatric Dermatology, 2012)
A 7-month-old little girl presented daily since the 7th day of life erythematous circinate lesions reminiscent of urticaria. The appearance at the age of 9 months of keratotic lesions led to diagnose erythrokeratodermia variabilis (EKV). The histological examination was compatible with the clinical diagnosis. The presence of circinate lesions resembling erythema gyratum repens led to the final diagnosis of EKV Cram-Mevorah.